Effects of Different Growth Regulators on Seed Germination and Vigor of Pot Marigold (Calendula Officinalis. L) - Singh, R; Tariyal, YS; Chauhan, JS (SAARC Journal of Agriculture, 2021)
Flowers are valued to mankind from the dawn of civilization. Flowers are used for various purposes in our day to day life like worshipping, religious and social functions, wedding, interior decoration, natural colours, dyes, scents and self adornment. Calendula officinalis is used as sudorific, blood refiner, blood sugar reducer and also use as anti-inflammatory skin. Seed testing is an essential step for evaluation of planting value of seeds, to minimize the risk of failure in planting low quality seeds. The importance of seed testing in agricultural crops has long been realized. Seed testing is also necessary to determine the need for drying and processing, to determine the quality standards under seed certification and seed law enforcement program, to identify seed quality problems and their probable causes and to provide basis for price fixation and consumer discrimination of seed lots etc.the 200ppm concentration of GA3 shows the significant and positive effect on the various germination and seedling parameters under study shows that GA3 is the best priming substance for the healthy and better germination in pot marigold. SAARC J. Agri., 18(2): 227-231 (2020)